1980
DOI: 10.2466/pr0.1980.46.1.327
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Chronic Self-Injurious Behavior by Withdrawal of Staff Attention

Abstract: Self-injurious behavior is frequently noted in institutionalized persons. Several treatment techniques have been attempted including medication, timeout, shock, aromatic ammonia, and adaptive clothing. Several authors have suggested extinction as an alternative technique. One problem with this technique is that self-injury may occur during the extinction period. The present study suggests that staff attention may maintain self-abusive behavior and withdrawal of this attention resulted in a rapid reduction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Failure to identify the maintaining variable(s) of an individual's maladaptive behavior, thus limiting the extinction component of the DRO, is one difficulty. Previous research (e.g., Lovaas & Simmons, 1969;Rose, Sloop, & Baker, 1980) has indicated that one way to reduce the frequency of behavior is to discontinue its reinforcing consequences, but in order to withhold delivery of these reinforcers, they must first be known.…”
mentioning
confidence: 99%
“…Failure to identify the maintaining variable(s) of an individual's maladaptive behavior, thus limiting the extinction component of the DRO, is one difficulty. Previous research (e.g., Lovaas & Simmons, 1969;Rose, Sloop, & Baker, 1980) has indicated that one way to reduce the frequency of behavior is to discontinue its reinforcing consequences, but in order to withhold delivery of these reinforcers, they must first be known.…”
mentioning
confidence: 99%